(untitled) (Biological Sciences - PJSIR, 1995)
The rice green leafhoppers, Nephotettix spp. (Homoptera: Cicadellidae is one of the most devastating pests of rice throughout the rice growing areas of Asia [1-4]. They act as an efficient vector of rice tungro virus, one of the most menacing disease of rice [1].